Strategic Management and Institutional Capacity Building in Islamic Higher Education: Evidence from the Emergence of a Postgraduate Program - Akhmadi Akhmadi (Education and Sociedad Journal, 2025)
The development of postgraduate education represents a critical stage in the transformation of higher education institutions, particularly within emerging Islamic universities seeking to enhance their academic capacity and intellectual contribution. However, limited studies have examined how strategic management functions as a mechanism for institutional capacity building in the establishment of postgraduate programs, especially in the context of Islamic higher education. This study addresses this gap by analysing the role of strategic management in supporting institutional transformation toward a research-based science education ecosystem. This research employs a qualitative field research design using a case study approach conducted at an Islamic higher education institution in Indonesia. Data were collected through semi-structured interviews, institutional observations, and document analysis, and analysed using thematic analysis to identify key patterns in leadership, planning, and organisational development processes. The findings reveal three main strategic foundations underpinning the successful establishment of the postgraduate program: visionary leadership, collaborative institutional planning, and academic resource mobilisation. These elements not only facilitated program implementation but also contributed to broader institutional capacity building through the strengthening of academic human resources, research culture, governance systems, and academic networks. Importantly, the study demonstrates that postgraduate education plays a transformative role in fostering a research-oriented academic environment, thereby supporting the development of a sustainable science education system.